PEMBELAJARAN PROJECT BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPAS KELAS V SEKOLAH DASAR (SD) NEGERI BLANG KUCAK - Maulina; Jumat Barus; Sambul Bahri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
He results of the preliminary observations in class V at SD Negeri Blang Kucak showed that many students had not reached the Minimum Completeness Criteria (KKM) in the IPAS subject. Therefore, an innovative approach is needed to increase student activity and learning outcomes. This study aims to describe teacher activities, student activities, and analyze student learning outcomes using the Project Based Learning (PjBL) model. This research is a Classroom Action Research (CAR) conducted in two cycles involving 13 students. Data were collected using observation sheets and tests. The results showed that teacher activity increased from 82.14% in the first cycle to 93.75% in the second cycle, and student activity increased from 77.86% to 94.64%. Student learning outcomes increased from 67.30% in the first cycle to 81.53% in the second cycle. The findings suggest that the implementation of the Project Based Learning model can improve student learning outcomes in IPAS for fifth-grade students at SD Negeri Blang Kucak.